(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A large body of research has shown a connection between COPD and occupational exposures. Coal miners are at increased risk for developing COPD if they breathe in the dust that is common in the industry. There were two sets of 81 people, spanning 36–60 years old, who worked for coal mining businesses and had stable chronic obstructive pulmonary disease (COPD). These individuals were identified at Stages II and III of the illness, respectively. A combination of conventional medical treatment and an integrated yoga curriculum was provided to the yoga group, whereas the control group only got conventional medical treatment. The participants did 90 minutes of yoga daily for 12 weeks. Yoga postures (asanas), breathing exercises (pranayama’s), relaxation techniques, and meditation are all a part of this time. The individuals in the control group were added to a yoga waiting list and given the opportunity to rejoin the programme after 12 weeks, if they were still interested. The following outcomes were noted in the yoga group after the intervention: CAT scores, dyspnea, fatigue, depression, anxiety, pulse rate, respiration rate, pain (P<0.001), and blood pressure (systolic and diastolic). When compared to coal miners getting conventional therapy for COPD, those who participated in a 12-week yoga course showed greater improvements in respiratory, autonomic, and psychophysiological parameters. Yoga has the ability to alleviate alleviate COPD symptoms by restoring the body’s natural defenses against stress and the brain.